2003
DOI: 10.1103/physrevlett.91.023002
|View full text |Cite
|
Sign up to set email alerts
|

Autler-Townes Splitting in the Multiphoton Resonance Ionization Spectrum of Molecules Produced by Ultrashort Laser Pulses

Abstract: We report for the first time the proper conditions to observe Autler-Townes splitting (ac-Stark splitting) from vibrationally coherent states belonging to the different electronic terms of a diatomic molecule. Wave packet dynamics simulations demonstrate that such a process is feasible by multiphoton resonance ionization of the molecule Na 2 with a single ultrashort intense laser pulse. With the ultrahigh time resolution of a femtosecond laser pulse, one can directly measure the absolute value of the transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 30 publications
3
49
0
Order By: Relevance
“…The simultaneous excitation/ionization technique therefore permits the use of photoelectron spectra as a fingerprint of the quantum mechanical phase imparted by the interaction with the shaped laser pulse. In passing, we note that similar effects are also present in molecular systems, although the vibrational dynamics tends to obscure the interference fringes (113,116,117). The potential of phase locked pulse sequences as a novel spectroscopic tool was demonstrated on single photon molecular transitions (118).…”
mentioning
confidence: 86%
“…The simultaneous excitation/ionization technique therefore permits the use of photoelectron spectra as a fingerprint of the quantum mechanical phase imparted by the interaction with the shaped laser pulse. In passing, we note that similar effects are also present in molecular systems, although the vibrational dynamics tends to obscure the interference fringes (113,116,117). The potential of phase locked pulse sequences as a novel spectroscopic tool was demonstrated on single photon molecular transitions (118).…”
mentioning
confidence: 86%
“…Qi et al pointed out that A‐T splitting induced by cw pulse can be used as a way to facilitate all‐optical control of molecular angular momentum alignment 14, 15. Sun and Lou demonstrated that one can observe the A‐T splitting in the photoelectron spectrum of a two‐level Na 2 system with a proper ultrashort laser pulse 16. We studied theoretically this kind of A‐T splitting in the photoelectron spectrum for a Li 2 molecular system using one‐dimension wave packet method 17.…”
Section: Introductionmentioning
confidence: 99%
“…(X = 40 nm). The partial recovery of the ground-state population before the end of the pulse we ascribe to incomplete single-cycle Rabi oscillations which can occur with short intense laser pulses [34,35].…”
Section: J(rf) = -[V'-(rf)vrt/r*(rf) -I/f*(rf)vri/(rf)] (3)mentioning
confidence: 83%